(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted across all the 14 districts of the Southern State of Kerala, during the Covid 19 pandemic. Google forms were used to collect demographic details, changes in food budget and lifestyle changes. The respondents aged between 18-45 years (N=1504), included students, working and non-working people and cut across all socio-economic groups. They hailed from various geographic locations since the State of Kerala includes regions of high altitudes, coastal regions, and plains. The Covid 19 brought about phases of lockdown and releases which affected the economy of the population. The adult workforce went through job losses, irregular and reduced income, all of which had an impact on the food budget of the families. This was felt most amongst those residing in high altitudes. Healthy practices like inclusion of Vitamin C rich foods, herbs and spices inculcating healthy cooking methods were adopted in more than half the population. Chi square test showed a statistical difference amongst the population, and it was found that those residing in rural areas, women folk, those with least education and the daily workers were more amenable to these new practices. Nearly 60% of the population initiated Kitchen Gardens. Weight gain was self-reported in nearly half the population (45%) and one-fourth (26%) of them reported a weight loss. The time spent on physical activity increased in 48% while one-third made no changes to their active time during the pandemic period. Social media emerged as the main source for disseminating information and the population relied on it for gaining health related information. Ethical clearance was obtained for this study.